Proof without words: The Sum - Chandoul, Amara; M. Sibih, Alalnod (International Journal of Psychosocial Rehabilitation, 2024)
Abstract—ObjectiveIn this note, we prove geometrically thatMethodology: In mathematics, a proof without words is a proof of an identity or mathematicalstatement, which can be demonstrated as self-evident by a diagram without any accompanyingexplanatory text. Using this method, we give the value of .